1999
DOI: 10.1034/j.1399-3011.1999.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the three‐dimensional structure on the deamidation reaction of ribonuclease A

Abstract: Kinetic data on the deamidation reaction of Asn67 in RNase A and of Asn3 in the two peptides Ac-Cys-Lys-Asn-Gly-Gln-Thr-Asn-Cys-NH2 and Ac-Cys(Me)-Lys-Asn-Gly-Gln-Thr-Asn-Cys(Me)-NH2, whose sequences are similar to that of the deamidation site in the enzyme, have been determined in a wide range of pH and buffer concentrations. The values of the observed rate constant (k) for the enzyme are markedly lower than those for the peptides. However, the k dependence on pH and buffers is similar for all three substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…Deamidation can be acid-or base-catalyzed (39,40), and the conversion of Peak Y to Peak X is found to be accelerated at a higher pH. The fact that the acceleration is only 3.2-fold and not 10-fold at pH 9.2 where [OH Ϫ ] is 10-fold higher relative to pH 8.2 is probably due the limited mobility of Asn 67 and Gly 68 within the folded structure (41,42).…”
Section: Discussionmentioning
confidence: 96%
“…Deamidation can be acid-or base-catalyzed (39,40), and the conversion of Peak Y to Peak X is found to be accelerated at a higher pH. The fact that the acceleration is only 3.2-fold and not 10-fold at pH 9.2 where [OH Ϫ ] is 10-fold higher relative to pH 8.2 is probably due the limited mobility of Asn 67 and Gly 68 within the folded structure (41,42).…”
Section: Discussionmentioning
confidence: 96%
“…Studies of b-turn model peptides 26,27 and some proteins 21,28,29 have demonstrated that b-turn secondary structures can stabilize Asn against deamidation, especially when Asn is located at the third position in a b-turn structure (except for type II turns). Such stabilization probably arises from structural constraints and reduced flexibility, which hinder formation of the favored conformation required for cyclic-imide formation.…”
Section: Crystal Structure Analysismentioning
confidence: 99%
“…For example, it has been shown recently that deamidation of glutamate dehydrogenase produced in Escherichia coli can be substantially reduced by temperature decreases during growth and during protein isolation (63). Additional studies have indicated the pH effect on the deamidation rate (77). Indeed, preliminary studies in our laboratory clearly indicate a decrease in the deamidation rate upon PA storage (as deduced from the reduction in the appearance of acidic isoforms) at pH 7.4 and at lower temperature concomitant with an improved biological stability of the protein.…”
Section: Pa Proteolytic Cleavage By Furin-asnmentioning
confidence: 99%